A high performance organic photovoltaic utilizing PEDOT:PSS and graphene oxide. Issue 34 (18th March 2016) - Kim, Hyeong Pil; Lee, Seung Joo; Mohd Yusoff, Abd Rashid bin; Jang, Jin
Abstract : Interface engineering may lead to a high performance organic photovoltaic as well as long lifetime. Abstract : Interface engineering may lead to a high performance organic photovoltaic as well as long lifetime. Incorporating the commonly used conducting polymer PEDOT:PSS with GO as an the anode interfacial layer, poly[[4, 8-bis[(2-ethylhexyl)oxy]benzo[1, 2- b :4, 5- b ′]dithiophene-2, 6-diyl][3-fluoro-2-[(2-ethylhexyl)carbonyl]thieno[3, 4- b ]thiophenediyl]] (PTB7):fullerene derivative (PC71 BM) bulk heterojunction (BHJ) organic photovoltaics (OPVs) were fabricated. This conventional OPV demonstrated a power conversion efficiency (PCE) of 7.53%, which has outperformed the highest reported PEDOT:PSS combined metal oxide, the highest reported efficiency with a solution processed PEDOT:PSS:GO interfacial layer as well as a PEDOT:PSS-based OPV (reference device). Moreover, the versatility of PEDOT:PSS:GO has also been demonstrated in the medium bandgap BHJ system employing poly[4, 8-bis(5-(2-ethylhexyl)thiophen-2-yl)benzo[1, 2- b ;4, 5- b ′]dithiophene-2, 6-diyl- alt -(4-(2-ethylhexyl)-3-fluorothieno[3, 4- b ]thiophene-)-2-carboxylate-2-6-diyl] paired with PC71 BM yielding an astonishing high PCE of 9.12%. We believe proper interface engineering could lead to high performance devices.